Nanolayered siRNA delivery platforms for local silencing of CTGF reduce cutaneous scar contraction in third-degree burns. (July 2016) - Castleberry, Steven A.; Golberg, Alexander; Sharkh, Malak Abu; Khan, Saiqa; Almquist, Benjamin D.; Austen, William G.; Yarmush, Martin L.; Hammond, Paula T.
Abstract: Wound healing is an incredibly complex biological process that often results in thickened collagen-enriched healed tissue called scar. Cutaneous scars lack many functional structures of the skin such as hair follicles, sweat glands, and papillae. The absence of these structures contributes to a number of the long-term morbidities of wound healing, including loss of function for tissues, increased risk of re-injury, and aesthetic complications. Scar formation is a pervasive factor in our daily lives; however, in the case of serious traumatic injury, scars can create long-lasting complications due to contraction and poor tissue remodeling. Within this report we target the expression of connective tissue growth factor (CTGF), a key mediator of TGFβ pro-fibrotic response in cutaneous wound healing, with controlled local delivery of RNA interference. Through this work we describe both a thorough in vitro analysis of nanolayer coated sutures for the controlled delivery of siRNA and its application to improve scar outcomes in a third-degree burn induced scar model in rats. We demonstrate that the knockdown of CTGF significantly altered the local expression of αSMA, TIMP1, and Col1a1, which are known to play roles in scar formation. The knockdown of CTGF within the healing burn wounds resulted in improved tissue remodeling, reduced scar contraction, and the regeneration of papillary structures within the healing tissue. This work adds support to a number of previous reports that indicate CTGF as a potential therapeutic target for fibrosis. Additionally, we believe that the controlled local delivery of siRNA from ultrathin polymer coatings described within this work is a promising approach in RNA interference that could be applied in developing improved cancer therapies, regenerative medicine, and fundamental scientific research.